Slurry for sanitary ceramic kiln and preparation method and application thereof

By coating the surface of the kiln board with a slurry made of ceramic clay, potassium, sodium feldspar powder and other materials, the problem of kiln board being eroded at high temperatures and bonding with ceramic products is solved, extending the life of the kiln board and improving the ceramics Product quality.

CN117534487BActive Publication Date: 2025-02-18JINGDEZHEN LEHUA CERAMICS SANITARY APPLIANCE CO LTD +1
View PDF 1 Cites 0 Cited by

Patent Information

Application Number
CN202311399443.8
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2023-10-26
Publication Date
2025-02-18
Estimated Expiration
2043-10-26

AI Technical Summary

Technical Problem

Existing kiln boards are easily eroded by ceramic glaze during high-temperature firing, resulting in hardening, peeling and cracking, affecting service life, and are prone to bonding with ceramic products, destroying product quality.

Method used

Provide a slurry for sanitary ceramic kilns, which has good high temperature resistance and isolation effect by mixing ceramic clay, potassium-sodium feldspar powder, dolomite, calcined alumina, non-calcined alumina, suspension agent and kaolin. The coating is coated on the surface of the kiln board to prevent the ceramic and kiln board from bonding.

Benefits of technology

It extends the service life of the kiln board, improves the firing quality of ceramic products, prevents the hardening of the kiln board and the bonding of ceramic products, and at the same time, the slurry has good suspension and prevents precipitation and agglomeration.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN117534487B_ABST
    Figure CN117534487B_ABST
Patent Text Reader

Abstract

The present invention belongs to the field of ceramic technology, and discloses a slurry for sanitary ceramic kilns, a preparation method and an application thereof. The raw materials for preparing the slurry for sanitary ceramic kilns of the present invention include: porcelain clay, potassium-sodium feldspar powder, dolomite, calcined alumina, non-calcined alumina, a suspending agent and kaolin. The slurry for sanitary ceramic kilns of the present invention introduces kaolin, calcined alumina and non-calcined alumina into the formula, so that the slurry has good high temperature resistance after drying, and can withstand high temperatures below 1400°C without peeling; at the same time, it can also prevent ceramic products and kiln plates from sticking together, play an insulating role, extend the service life of the kiln plates, and improve the firing quality of ceramic products; in addition, the suspending agent is used to make the slurry have good suspension properties, and it is not easy to precipitate and agglomerate, which ensures the coating properties of the slurry.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of ceramics, and in particular relates to a slurry for a sanitary ceramic kiln, and a preparation method and application thereof. Background Art

[0002] Sanitary ceramics are generally sintered in kilns. When the ceramics are fired, kiln plates are needed to support the products. At present, the materials of kiln plates are mainly silicon carbide and mullite, most of which contain a lot of free silicon (about 15%), and they can generally withstand high temperatures of about 1700°C. However, during the use of the kiln, the glaze on the ceramic products will flow onto the kiln plates at high temperatures, stick to the kiln plates, and gradually penetrate into the inside of the kiln plates. After repeated high-temperature firing in the kiln, the eroded kiln plates will harden, peel, and crack, affecting their service life. At the same time, the eroded kiln plates are also prone to bonding with ceramic products during the sintering process, damaging the ceramic products and affecting the firing quality of the ceramic products. Summary of the invention

[0003] The present invention aims to solve at least one of the technical problems existing in the above-mentioned prior art. To this end, the present invention provides a slurry for a sanitary ceramic kiln and a preparation method and application thereof; the slurry is applied to the surface of the kiln plate, has good high temperature resistance after drying, and acts as an insulator to prevent the ceramic product and the kiln plate from sticking together, effectively protecting the kiln plate and the ceramic product, extending the service life of the kiln plate, and improving the firing quality of the ceramic product.

[0004] A first aspect of the present invention provides a slurry, wherein raw materials for preparing the slurry include: china clay, potassium and sodium feldspar powder, dolomite, calcined alumina, non-calcined alumina, a suspending agent and kaolin.

[0005] According to some embodiments of the present invention, the raw materials for preparing the slurry include, by weight: 2-10 parts of china clay, 1-15 parts of potassium and sodium feldspar powder, 0.1-2 parts of dolomite, 50-80 parts of calcined alumina, 0.1-5 parts of uncalcined alumina, 0.5-3 parts of suspending agent and 1-25 parts of kaolin.

[0006] According to some embodiments of the present invention, the raw materials for preparing the slurry include, by weight: 3-8 parts of china clay, 4-12 parts of potassium and sodium feldspar powder, 0.8-1.4 parts of dolomite, 68-80 parts of calcined alumina, 1-3 parts of uncalcined alumina, 1-2 parts of suspending agent and 5-15 parts of kaolin.

[0007] According to some embodiments of the present invention, the mesh size of the non-calcined alumina is 80-120 meshes. The present invention further improves the suspension and high temperature resistance of the slurry by optimizing the mesh size of the non-calcined alumina; specifically, if the particle size of the non-calcined alumina is too coarse, precipitation and stratification are likely to occur, and if it is too fine, sintering is likely to occur.

[0008] According to some embodiments of the present invention, the suspension agent includes the following chemical components by mass percentage: 0.1-2% silicon oxide, 0.01-1% aluminum oxide, 0.01-1% iron oxide, 45-60% calcium oxide, 0.1-2% magnesium oxide, 0.1-0.5% potassium oxide, and the ignition loss is 35-50%. Specifically, the model of the suspension agent is 7060S; compared with other types of suspension agents, the present invention uses this type of suspension agent, which is more suitable for the slurry system of the present invention, so that the slurry is not easy to precipitate and agglomerate, while other types of suspension agents have a shorter precipitation and agglomeration time and a more serious precipitation problem.

[0009] According to some embodiments of the present invention, the slurry includes the following chemical components, measured by mass percentage: 10-30% silicon oxide, 65-85% aluminum oxide, 0.05-1% iron oxide, 0.1-1.5% calcium oxide, 0.1-2% magnesium oxide, 0.1-1% potassium oxide, 0.1-1% sodium oxide, and the loss on ignition is 0.5-3%.

[0010] The second aspect of the present invention provides a method for preparing the slurry of the present invention, comprising the following steps:

[0011] The china clay, potassium-sodium feldspar powder, dolomite, calcined alumina, non-calcined alumina, a suspending agent and kaolin are mixed to obtain a mixture;

[0012] The mixed material is mixed with water and stirred evenly to obtain the slurry.

[0013] According to some embodiments of the present invention, the mass of the water accounts for 55-60% of the mass of the mixed material.

[0014] According to some embodiments of the present invention, the specific gravity of the slurry is 1.35-1.45 g / mL.

[0015] According to some embodiments of the present invention, after obtaining the slurry, the step further includes passing the slurry through a 60-100 mesh sieve.

[0016] A third aspect of the present invention provides a kiln plate, on which a coating is coated, and the coating is obtained by drying the slurry described in the present invention.

[0017] Compared with the prior art, the beneficial effects of the present invention are as follows:

[0018] The slurry used for the sanitary ceramic kiln of the present invention introduces kaolin, calcined alumina and non-calcined alumina into the formula, so that the slurry has good high temperature resistance after drying, can withstand high temperatures below 1400°C without peeling, and can also prevent the ceramic product and the kiln plate from sticking together, play an insulating role, extend the service life of the kiln plate, and improve the firing quality of the ceramic product; in addition, the suspending agent is combined to make the slurry have good suspension properties, not easy to precipitate and agglomerate, and ensure the coating property of the slurry. BRIEF DESCRIPTION OF THE DRAWINGS

[0019] The present invention will be further described below in conjunction with the accompanying drawings and embodiments.

[0020] Figure 1 The slurry of Example 1 and Comparative Example 3 is a physical picture after being left to stand for a period of time;

[0021] Figure 2 This is a photo of a kiln plate made by coating the slurry of Example 1 after being used in a high-temperature kiln for 7 days;

[0022] Figure 3 This is a real picture of the kiln plate made by coating the slurry of Comparative Example 1 after being used in a high-temperature kiln for 7 days. DETAILED DESCRIPTION

[0023] The present invention is further described in detail below by specific examples. The raw materials, reagents or devices used in the examples can be obtained from conventional commercial sources or by prior art methods unless otherwise specified. Unless otherwise specified, the experiments or test methods are conventional methods in the art.

[0024] Example 1

[0025] A slurry comprises the following raw materials in parts by weight: 5 parts of china clay, 10 parts of potassium-sodium feldspar powder, 1 part of dolomite, 70 parts of calcined alumina, 1.5 parts of non-calcined alumina, 1.5 parts of suspending agent and 11 parts of kaolin.

[0026] Among them, the model of the suspending agent is 7060S, which includes the following chemical components in mass percentage: 1.2% silicon oxide, 0.6% aluminum oxide, 0.2% iron oxide, 51% calcium oxide, 1.8% magnesium oxide, 0.2% potassium oxide, and the loss on ignition is 45%; the mesh size of the non-calcined aluminum oxide is 100 mesh.

[0027] The slurry includes the following chemical components in percentage by mass: 17.9% silicon oxide, 77% aluminum oxide, 0.4% iron oxide, 0.8% calcium oxide, 0.6% magnesium oxide, 0.7% potassium oxide, 0.3% sodium oxide, and the loss on ignition is 2.3%.

[0028] The specific preparation process of the above slurry is as follows:

[0029] S1, according to the above ratio, china clay, potassium and sodium feldspar powder, dolomite, calcined alumina, non-calcined alumina, suspending agent and kaolin are mixed to obtain a mixture;

[0030] S2. Add 55% of the water by mass of the mixture to the mixture in step S1, control the slurry specific gravity to 1.38 g / mL, stir evenly, and then pass through an 80-mesh sieve to obtain a slurry.

[0031] Example 2

[0032] A slurry comprises the following raw materials in parts by weight: 8 parts of china clay, 8 parts of potassium-sodium feldspar powder, 1.2 parts of dolomite, 68 parts of calcined alumina, 1.3 parts of non-calcined alumina, 1.5 parts of suspending agent and 12 parts of kaolin.

[0033] Among them, the model of the suspending agent is 7060S, which includes the following chemical components in mass percentage: 1.26% silicon oxide, 0.57% aluminum oxide, 0.18% iron oxide, 49.8% calcium oxide, 1.76% magnesium oxide, 0.23% potassium oxide, and the loss on ignition is 46.2%; the mesh size of the non-calcined aluminum oxide is 80 mesh.

[0034] The slurry includes the following chemical components in mass percentage: 18.65% silicon oxide, 76.3% aluminum oxide, 0.42% iron oxide, 0.7% calcium oxide, 0.7% magnesium oxide, 0.68% potassium oxide, 0.2% sodium oxide, and the loss on ignition is 2.35%.

[0035] The specific preparation process of the above slurry is as follows:

[0036] S1, according to the above ratio, china clay, potassium and sodium feldspar powder, dolomite, calcined alumina, non-calcined alumina, suspending agent and kaolin are mixed to obtain a mixture;

[0037] S2. Add 56% of the water by mass of the mixture to the mixture in step S1, control the slurry specific gravity to 1.35 g / mL, stir evenly, and then pass through an 85-mesh sieve to obtain a slurry.

[0038] Example 3

[0039] A slurry comprises the following raw materials in parts by weight: 4 parts of china clay, 12 parts of potassium-sodium feldspar powder, 1.2 parts of dolomite, 73 parts of calcined alumina, 1.5 parts of non-calcined alumina, 1.3 parts of suspending agent and 7 parts of kaolin.

[0040] Among them, the model of the suspending agent is 7060S, which includes the following chemical components in mass percentage: 1.16% silicon oxide, 0.61% aluminum oxide, 0.3% iron oxide, 50.8% calcium oxide, 1.6% magnesium oxide, 0.23% potassium oxide, and the loss on ignition is 45.3%; the mesh size of the non-calcined aluminum oxide is 120 mesh.

[0041] The slurry includes the following chemical components in percentage by mass: 16.15% silicon oxide, 78% aluminum oxide, 0.6% iron oxide, 0.7% calcium oxide, 0.8% magnesium oxide, 0.8% potassium oxide, 0.5% sodium oxide, and the loss on ignition is 2.45%.

[0042] The specific preparation process of the above slurry is as follows:

[0043] S1, according to the above ratio, china clay, potassium and sodium feldspar powder, dolomite, calcined alumina, non-calcined alumina, suspending agent and kaolin are mixed to obtain a mixture;

[0044] S2. Add 58% of the water by mass of the mixture to the mixture in step S1, control the slurry specific gravity to 1.45 g / mL, stir evenly, and then pass through a 90-mesh sieve to obtain a slurry.

[0045] Comparative Example 1

[0046] A slurry comprises the following raw materials in parts by weight: 60 parts of calcined alumina and 40 parts of kaolin.

[0047] The specific preparation process of the above slurry is as follows:

[0048] S1. Mixing calcined alumina and kaolin according to the above ratio to obtain a mixture;

[0049] S2. Add 55% of the water by mass of the mixture to the mixture in step S1, control the slurry specific gravity to 1.38 g / mL, stir evenly, and then pass through an 80-mesh sieve to obtain a slurry.

[0050] Comparative Example 2 (the difference from Example 1 is that no non-calcined alumina is added)

[0051] A slurry comprises the following raw materials in parts by weight: 5 parts of china clay, 10 parts of potassium-sodium feldspar powder, 1 part of dolomite, 71.5 parts of calcined alumina, 1.5 parts of suspending agent and 11 parts of kaolin.

[0052] Among them, the model of the suspending agent is 7060S, which includes the following chemical components in mass percentage: 1.2% silicon oxide, 0.6% aluminum oxide, 0.2% iron oxide, 51% calcium oxide, 1.8% magnesium oxide, 0.2% potassium oxide, and the loss on ignition is 45%.

[0053] The preparation method of the slurry of Comparative Example 2 is the same as that of Example 1.

[0054] Comparative Example 3 (the difference from Example 1 is that kaolin is not added)

[0055] A slurry comprises the following raw materials in parts by weight: 5 parts of china clay, 10 parts of potassium-sodium feldspar powder, 1 part of dolomite, 80 parts of calcined alumina, 2.5 parts of non-calcined alumina and 1.5 parts of a suspending agent.

[0056] Among them, the model of the suspending agent is 7060S, which includes the following chemical components in mass percentage: 1.2% silicon oxide, 0.6% aluminum oxide, 0.2% iron oxide, 51% calcium oxide, 1.8% magnesium oxide, 0.2% potassium oxide, and the loss on ignition is 45%; the mesh size of the non-calcined aluminum oxide is 100 mesh.

[0057] The preparation method of the slurry of Comparative Example 3 is the same as that of Example 1.

[0058] Suspension performance test

[0059] The slurries prepared in Examples 1-3 and Comparative Examples 1-3 were placed in beakers respectively and allowed to stand for a period of time to observe whether there was precipitation or stratification. The results are shown in Tables 1 and Figure 1 shown.

[0060] Table 1

[0061] Group Initial state 15 minutes 30 minutes 60 minutes 120 minutes 240 minutes Example 1 No precipitation No precipitation No precipitation No precipitation No precipitation Sedimentation Example 2 No precipitation No precipitation No precipitation No precipitation No precipitation Sedimentation Example 3 No precipitation No precipitation No precipitation No precipitation No precipitation Sedimentation Comparative Example 1 No precipitation No precipitation No precipitation Sedimentation / / Comparative Example 2 No precipitation No precipitation No precipitation Sedimentation / / Comparative Example 3 No precipitation Sedimentation / / / /

[0062] like Figure 1 As shown, Figure 1 (a) is a physical picture of the slurry of Example 1 after being left to stand for 120 minutes, and it can be seen that there is no precipitation layer; Figure 1 (b) is a real picture of the slurry of comparative example 3 after being left to stand for 15 minutes, and it can be seen that obvious precipitation and stratification have occurred. As can be seen from Table 1, the slurry of the present invention has good suspension stability, is not prone to precipitation and stratification, and can better meet production needs.

[0063] High temperature resistance test

[0064] The mixtures of Examples 1-3 and Comparative Examples 1-3 were pressed into cakes, and fired at 1200°C ± 10°C to obtain samples. The samples were tested according to the water absorption test method of reference standard GB / T 6952-2015 sanitary ceramics. The greater the water absorption of the sample, the better the high temperature resistance. The test results are shown in Table 2.

[0065] Table 2

[0066] Group Water absorption (%) Example 1 26 Example 2 24 Example 3 25 Comparative Example 1 14 Comparative Example 2 10 Comparative Example 3 18

[0067] It can be seen from the data in Table 2 that the raw materials used in the preparation of the slurry of the present invention have better high temperature resistance.

[0068] Application Example 1

[0069] A kiln plate is coated with a coating, wherein the coating is prepared by drying the slurry of Example 1.

[0070] Application Example 2

[0071] A kiln plate is coated with a coating, wherein the coating is prepared by drying the slurry of Example 2.

[0072] Application Example 3

[0073] A kiln plate is coated with a coating, wherein the coating is prepared by drying the slurry of Example 3.

[0074] Application Comparative Example 1

[0075] A kiln plate is coated with a coating, wherein the coating is prepared by drying the slurry of comparative example 1.

[0076] Application Comparative Example 2

[0077] A kiln plate is coated with a coating, wherein the coating is prepared by drying the slurry of comparative example 2.

[0078] Application Comparative Example 3

[0079] A kiln plate is coated with a coating, wherein the coating is prepared by drying the slurry of comparative example 3.

[0080] Kiln plate performance test

[0081] The kiln plate of Example 1 and the kiln plate of Comparative Example 1 were fired at a high temperature (1400°C) in a kiln for 7 days, and the actual pictures are as follows: Figure 2 and Figure 3 As shown. Figure 2 It can be seen that the coating on the kiln plate of Application Example 1 is basically the same as the state before firing, flat and uniform; Figure 3 It can be seen that the coating on the kiln plate of comparative example 1 is obviously agglomerated and hardened, and even falls off in some places. It can be seen that the coating formed by the slurry of the present invention has better high temperature resistance.

[0082] In addition, there is no significant difference in the high temperature resistance of the kiln plates of Example 2-3 and Example 1; while the high temperature resistance of the kiln plates of Comparative Examples 2-3 is significantly reduced. After being fired in a kiln at high temperature (1400°C) for 7 days, the results are similar to the test results of the kiln plates of Comparative Example 1, and the coating also has problems of agglomeration, hardening and falling off.

[0083] The preferred embodiments of the present invention are specifically described above, but the invention is not limited to the embodiments. Those skilled in the art may make various equivalent modifications or substitutions without violating the spirit of the invention. These equivalent modifications or substitutions are all included in the scope defined by the claims of this application.

Claims

1. A slurry, characterized in that: The raw materials for preparing the slurry are composed of china clay, potassium and sodium feldspar powder, dolomite, calcined alumina, non-calcined alumina, suspending agent, kaolin and water; According to the weight percentage, the china clay is 2-10 parts, the potassium and sodium feldspar powder is 1-15 parts, the dolomite is 0.1-2 parts, the calcined alumina is 50-80 parts, the non-calcined alumina is 0.1-5 parts, the suspending agent is 0.5-3 parts and the kaolin is 1-25 parts; The suspension agent comprises the following chemical components in terms of mass percentage: 0.1-2% silicon oxide, 0.01-1% aluminum oxide, 0.01-1% iron oxide, 45-60% calcium oxide, 0.1-2% magnesium oxide, 0.1-0.5% potassium oxide, and the loss on ignition is 35-50%; The mesh number of the non-calcined alumina is 80-120 mesh.

2. The slurry according to claim 1, characterized in that Calculated by weight, china clay is 3-8 parts, potassium and sodium feldspar powder is 4-12 parts, dolomite is 0.8-1.4 parts, calcined alumina is 68-80 parts, non-calcined alumina is 1-3 parts, suspending agent is 1-2 parts and kaolin is 5-15 parts.

3. The slurry according to claim 1, characterized in that The slurry includes the following chemical components in percentage by mass: 10-30% silicon oxide, 65-85% aluminum oxide, 0.05-1% iron oxide, 0.1-1.5% calcium oxide, 0.1-2% magnesium oxide, 0.1-1% potassium oxide, 0.1-1% sodium oxide, and the loss on ignition is 0.5-3%.

4. The method for preparing the slurry according to any one of claims 1 to 3, characterized in that: The following steps are involved: The china clay, potassium-sodium feldspar powder, dolomite, calcined alumina, non-calcined alumina, a suspending agent and kaolin are mixed to obtain a mixture; The mixed material is mixed with water and stirred evenly to obtain the slurry.

5. The preparation method according to claim 4, characterized in that: The mass of the water accounts for 55-60% of the mass of the mixed material.

6. The preparation method according to claim 4, characterized in that: The specific gravity of the slurry is 1.35-1.45 g / mL.

7. A kiln plate, characterized in that: The kiln plate is coated with a coating, and the coating is obtained by drying the slurry according to any one of claims 1 to 3.

Citation Information

Patent Citations

  • Coating for improving surface precision of layered extrusion molding ceramic, preparation method and treatment method

    CN116375492A